2017
DOI: 10.1080/10926771.2017.1308982
|View full text |Cite
|
Sign up to set email alerts
|

Betrayed? That’s Me: Implicit and Explicit Betrayed Self-Concept in Young Adults Abused as Children

Abstract: Attenuated awareness of betrayal, or "betrayal blindness," is a proposed survival mechanism in relationships where awareness of betrayal will mobilize confront-or-withdraw responses that jeopardize a needed relationship. Empirical tests of betrayal blindness and its effects are hampered by the methodological conundrum of how to measure an absence of awareness. The purpose of this study was to evaluate the validity of a novel empirical method to measure implicit betrayed self-concept, the first step in a long-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For example, one study found that a self + traumatization IAT predicted PTSD symptoms over and above the extent of trauma exposure and explicit cognitive measures (Lindgren et al 2013b). In line with this finding, as assessed by an IAT, trauma frequency and severity may be associated with stronger implicit associations of violence + negativity (Bluemke et al 2017), self + anxiety and self + depression ( Johnson et al 2011, van Harmelen et al 2010, and self + betrayal (Delker & Freyd 2017). Surprisingly, for participants who experienced prior sexual abuse, relatively greater sex + aggression associations on an IAT were negatively associated with past trauma frequency and current effects of trauma (Reed et al 2011).…”
Section: Posttraumatic Stress Disorder: Empirical Evidencementioning
confidence: 56%
“…For example, one study found that a self + traumatization IAT predicted PTSD symptoms over and above the extent of trauma exposure and explicit cognitive measures (Lindgren et al 2013b). In line with this finding, as assessed by an IAT, trauma frequency and severity may be associated with stronger implicit associations of violence + negativity (Bluemke et al 2017), self + anxiety and self + depression ( Johnson et al 2011, van Harmelen et al 2010, and self + betrayal (Delker & Freyd 2017). Surprisingly, for participants who experienced prior sexual abuse, relatively greater sex + aggression associations on an IAT were negatively associated with past trauma frequency and current effects of trauma (Reed et al 2011).…”
Section: Posttraumatic Stress Disorder: Empirical Evidencementioning
confidence: 56%
“…Veterans with posttraumatic disorders, for example, frequently report disillusionment with human nature and being alienated from the civilian world (Brewin et al, 2011). Alienation is strongly associated with posttraumatic symptoms in survivors of many different kinds of trauma (McIlveen et al, 2020), as is being betrayed by caregivers and those in authority (Delker & Freyd, 2017; Finkelhor & Browne, 1985; Smith & Freyd, 2014).…”
Section: Foundations For a Theory Of Cptsd: Identity Memory And Emoti...mentioning
confidence: 99%
“…Although research has found evidence of a link between negative self-association and childhood interpersonal trauma, the link is weak (e.g., Cohen’s d = .12; Van Harmelen et al, 2010). Others have reported that traumatization does not correlate with negative self-associations (Engelhard et al, 2007; Lindgren et al, 2013) or that the link might be masked when various adverse relational experiences are not differentiated and controlled for in the analysis (Delker & Freyd, 2017). Notably, an inverse correlation was found between child physical abuse and a self-disgust association (Rüsch et al, 2011).…”
mentioning
confidence: 99%